RELATIONSHIP OF EMOTIONAL INTELLIGENCE WITH SELF- ESTEEM AMONG ADOLESCENTS - Kaur Tajpreet; S K Maheshwari (Indian Journal of Psychiatric Nursing)
Adolescence is a time in which adolescents give way to intense emotional relationships and find self concept and build self esteem. Literature reports that 55%-63% of adolescents are at low level of emotional intelligence which results in low self esteem. The present survey was conducted to assess the relationship between emotional intelligence and self esteem among 200 randomly selected (lottery method) students from six conveniently selected schools of dist. Faridkot, Punjab by using the emotional intelligence scale (EIS), Rosernberg self- esteem rating scale and socio demographic data sheet. Emotional intelligence scores were compared with self esteem scores. The Pearson's product moment correlation, t-test and ANOVA were used for statistical analysis. The results showed that emotional intelligence and self esteem had significant positive correlation at the level of 0.01. Study concluded that emotionally intelligent adolescents have high self esteem. Adolescents should be early identified early for emotionally immaturity and can be managed with help of school health nurse in school setting by providing different strategies for emotional intelligence and thus enhancing the self esteem.